Evaluation of heavy metal contamination in groundwater samples from Kapas Island, Terengganu, Malaysia - Mohd Isa, Noorain; Aris, Ahmad Zaharin; Lim, Wan Ying; Sulaiman, Wan Nor Azmin; Praveena, Sarva Mangala (Springer, 2014)
An attempt has been made to delineate the hydrochemistry for a small island based on the major ions and heavy metal concentrations. In this investigation, six sampling campaigns were conducted to measure the concentrations of major ions (Ca, Mg, Na, K, HCO3, Cl, and SO4) and heavy metals (Zn, Cr, Pb, Mn, As, and Cu) in groundwater samples collected from seven sampling stations (boreholes) located on Kapas Island, Terengganu, Malaysia. The distribution of major ions is illustrated by a piper plot where Ca–HCO3 is the dominant type. In addition, the concentrations of heavy metals demonstrate that Mn shows as being the highest concentrated heavy metal in the groundwater sampled in the sampling campaigns; the average Mn content in groundwater sampled was 54.05 μg/L. However, a comparison of the heavy metal (Mn, Cr, Zn, As, Pb, and Cu) concentrations in groundwater samples with the Drinking Water Quality Standard prescribed by World Health Organization reveals that none of these heavy metals exceeded the recommended threshold limits. The principal component analyses (PCA) extracted four components that control the groundwater chemistry. Components 1 and 2 from the PCA analyses extracted approximately 52.11 % of the total variance, which represent the heavy metals (As and Mn) and physical parameters (pH, redox potential, electrical conductivity, temperature, and total dissolved solids). Based on the output of the PHREEQC hydrogeochemical software, several species of heavy metals exist, in which the dominant species found are Mn2+, PbCO3, Cu(OH)2, and Zn+.